Studi Fenomenologi: Pengalaman Pasangan Penderita HIV Dalam Mempertahankan Status HIV Negatif di Poliklinik Puspa RSUD Tarakan Jakarta - Suryati Suryati; Dewi Purnamawati; Wati Jumaiyah (FORIKES, 2021)
A phenomenological study has been conducted to explore various experiences of partners with HIV in maintaining negative status. The study data were obtained from 6 participants, collected through in-depth unstructured interviews at the Puspa polyclinic RSUD Tarakan Jakarta. The purpose of this study was to find out how deeply the experiences of partners with HIV in maintaining negative status. Interviews were recorded and then made in the form of interview transcripts. The results revealed variations in the experiences of the participants in maintaining a negative status. One in 6 participants in this study had a good knowledge of HIV, saying that HIV is a naughty disease caused by playing with women and can also be naughty because of drugs. Other participants still did not understand or know about HIV and considered HIV a taboo disease. Nonetheless, the behavior of the serodiscordant pair was largely good. Seen among them, they use contraceptives, namely condoms when having intercourse and each partner is serodiscordant taking ARV drugs regularly, in preventing and alleviating transmission. It was also seen that each participant tested negative, based on CD4 cell counts for all participants who were routinely checked. This is also to alleviate the stigma and discrimination they receive from their families and society.Keywords: experience; serodsicordan; maintaining a negative statusABSTRAKSuatu studi fenomenologi telah dilakukan untuk mengeksplorasi berbagai pengalaman pasangan penderita HIV dalam mempertahankan status negative. Data studi ini diperoleh dari 6 partisipan, dikumpulkan melalui wawancara tidak terstruktur yang mendalam di poliklinik Puspa RSUD Tarakan Jakarta. Tujuan penelitian ini ialah untuk mengetahui bagaimana secara mendalam pengalaman pasangan penderita HIV dalam mempertahankan status negatif. Wawancara direkam kemudian dibuat dalam bentuk transkip wawancara. Hasil penelitian mengungkapkan variasi berbagai pengalaman partisipan dalam mempertahankan status negative. Satu dari 6 partisipan dalam studi ini mempunyai pengetahuan yang baik tentang HIV, mengatakan bahwa HIV adalah penyakit nakal dikarenakan main perempuan dan bisa juga nakal karena narkoba. Partisipan lainnya masih belum memahami atau mengetahui tentang HIV dan menganggap HIV adalah penyakit yang tabu. Walaupun demikian, perilaku pasangan serodiskordan sebagian besar sudah baik. Dilihat diantaranya mereka menggunakan alat kontrasepsi yaitu kondom saat melakukan hubungan dan masing-masing pasangan serodiskordan minum obat ARV secara rutin, dalam pencegahan maupun meringankan penularan. Juga terlihat dari masing-masing partisipan dinyatakan negatife, berdasarakan pemeriksaan CD4 bagi semua partisipan yang rutin diperiksa. Hal ini juga untuk meringankan stigma dan diskriminasi yang mereka terima dari keluarga maupun dari masyarakat.Kata kunci: pengalaman; serodsikor; mempertahankan status negatif